2019
DOI: 10.1111/jfpp.13905
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of ultrasonication and hydration temperature on water absorption of barley: Analysis, modeling, kinetics, optimization, and thermodynamic parameters of the process

Abstract: Higher hydration temperature is commonly applied to enhance hydration process of grains. Ultrasound technology is recently employed as an alternative approach for enhancement of the process. This paper describes the combined effect of ultrasonication and hydration temperature on water absorption of barley grain during hydration process. The process was carried out at five hydration temperatures of 20, 30, 40, 50, and 60°C in hydration conditions named control (without ultrasound treatment) and ultrasonication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
4
12
0
Order By: Relevance
“…It increases the diffusion process and results in higher moisture content in the millet grains [18] . Though the moisture content of the optimized ultrasound hydrated finger millet was close to that of conventionally hydrated samples, ultrasound treatment alone is not sufficient to achieve maximum hydration [7] . Significant differences ( P < 0.05 ) were observed for the various quality characteristics of optimized ultrasound hydrated and conventionally hydrated finger millets.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…It increases the diffusion process and results in higher moisture content in the millet grains [18] . Though the moisture content of the optimized ultrasound hydrated finger millet was close to that of conventionally hydrated samples, ultrasound treatment alone is not sufficient to achieve maximum hydration [7] . Significant differences ( P < 0.05 ) were observed for the various quality characteristics of optimized ultrasound hydrated and conventionally hydrated finger millets.…”
Section: Resultsmentioning
confidence: 87%
“…Ultrasound exposure at higher amplitude for extended time disrupts and dislodge the cells creating microcavities and results in higher mass transfer by diffusion. This helps in improving hydration [6] , [7] , [15] , [16] , [17] . The higher values of R 2 (0.96), adj.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrasound technology has shown good results enhancing different mass transfer processes, especially the grain hydration process. For instance, this technology accelerated the hydration of chick peas (Yildirim, Öner, & Bayram, ), common beans (Ulloa et al, ), sorghum kernels (Patero & Augusto, ), navy beans (Ghafoor, Misra, Mahadevan, & Tiwari, ), white kidney beans (Miano, Sabadoti, & Augusto, ), barley kernels (Shafaei, Nourmohamadi‐Moghadami, & Kamgar, ), among others. Ultrasound consists of using acoustic waves with frequencies between 20 and 500 kHz and power higher than 1 W/cm 2 , which by both direct and indirect effects causes physical–chemical and structural changes on food (Awad, Moharram, Shaltout, Asker, & Youssef, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, another strategy (ultrasonication) has been employed to proliferate water absorption of agricultural food products. Literature screening process confirmed that ultrasonication strategy was successfully utilized for soaking process of rice (Li et al, 2019; Wambura, Yang, & Wang, 2008), chickpea (Yildirim, Bayram, & Oner, 2012; Yildirim & Oner, 2015; Yildirim, Oner, & Bayram, 2010; Yildirim, Oner, & Bayram, 2011; Yildirim, Oner, & Bayram, 2013), bean (Ghafoor, Misra, Mahadevan, & Tiwari, 2014; Lopez et al, 2017; Miano & Augusto, 2018a; Miano, Pereira, et al, 2016; Miano, Rojas, & Augusto, 2019a; Miano, Sabadoti, & Augusto, 2018; Miano, Sabadoti, & Augusto, 2019; Ulloa et al, 2015), sorghum (Miano, Ibarz, et al, 2016; Patero & Augusto, 2015), melon (Miano, Ibarz, et al, 2016), sea cucumber (Zhang et al, 2016a, 2016b), carrot (Ricce, Rojas, Miano, Siche, & Augusto, 2016), corn (Miano, Ibarz, & Augusto, 2017), wheat (Guimaraes, Polachini, Augusto, & Telis‐Romero, 2020; Shafaei, Nourmohamadi‐Moghadami, & Kamgar, 2018; Shafaei, Nourmohamadi‐Moghadami, Rahmanian‐Koushkaki, & Kamgar, 2019), potato (Miano, Rojas, & Augusto, 2019b), barley (Borsato, Jorge, Mathias, & Jorge, 2019; Carvalho, Polachini, Darros‐Barbosa, Bon, & Telis‐Romero, 2018; Shafaei, Nourmohamadi‐Moghadami, & Kamgar, 2019), pumpkin (Rojas, Silveira, & Augusto, 2020), sesame (Shafaei, Nourmohamadi‐Moghadami, et al, 2021), and paddy (Kalita, Jain, Srivastava, & Goud, 2021). In these works, modeling of ultrasonication‐assisted soaking process of the products was commonly fulfilled with respect to soaking time using above‐mentioned nonlinear models for certain soaking temperatures and, constants and coefficients of the models varied with variations in soaking temperature.…”
Section: Introductionmentioning
confidence: 99%